Sanitising the City: Exploring Hegemonic Gentrification in London's Soho. (August 2016) - Sanders-Mcdonagh, Erin; Peyrefitte, Magali; Ryalls, Matt
This article will explore the gentrification of Soho, reflecting on ethnographic research undertaken in the area over the past fifteen months, to argue that the recent social, political, and economic changes in Soho must be understood in relation to private, marketized and globalized neoliberal capitalist forces. We argue that the changes to the area result in a heavily-weighted form of gentrification that works to actively and knowingly sanitize the city, removing 'undesirable' people and venues from the area. As such, we propose to define this process as 'hegemonic gentrification', and distinguish this from other forms of gentrification in order to understand the different processes that underpin these specific changes, and more broadly, it allows us to problematize these changes as regards to the 'right to the city', and to expand current understandings in a way that allows for a more nuanced analysis of urban gentrification and its impacts within neolibreral capitalism.